ASSESSMENT OF USING ARC GIS TO DETERMINE SOMELANDFORMS IN AL-SALMAN DEPRESSION/SOUTH IRAQ - Al-Saedi, Z.; Ahmad, W. (Iraqi Journal of Science, 2024)
The study area lies south west to Al- Muthanna governorate; it is about 140 kmaway from the governorate center. The study area is about 1296 km2, betweenlongitudes 44° 24` – 44° 41` Easting, Latitude 30° 18` – 30° 44` Northing. Spacedata used in this research is Landsat 7 images by the sensors ETMÑ 2000 beside theDEM image product by Shuttle Radar Topography Mission SRTM. Using thepresent technique we can recognize the landforms in the area depending oncharacteristics in Arc GIS program and the ability in the program, as well as,accuracy of the program which become simulating with features in field. The sketchtechnique was done by using DEM image associated with tools box in Arc GISprogram. In order to increase the accuracy of the results we used the "Hill Shade"method and adding some orders like "Aspect" and "Sink".From this technique we conclude that Hill shade method enables us to recognizeddepressions, structural plains, and pediments. And from Aspect we can recognize theslope direction while the Sink order we can recognized the sinkholes in the studyarea.